GAZZÂLİ'DE KALB-AKIL İLİŞKİSİ - ACUN, FATİH (Fırat Üniveristesi, 2012)
Gazzâli XI. ve XII. asırlarda yaşamış bir İslam düşünürüdür. Gazzâli yaşadığı çağı Ehl-i Sünnet anlayışıyla yorumlayan bir âlimdir. Bu aydın hem kendi yaşadığı döneme hem de günümüz Müslümanlarına ışık tutmaktadır. Gazzâli yaşadığı dönemin geçerli olan ilim dallarını araştırmış ve o ilim dallarında uzman olmuştur. Gazzâli'nin hayatı, yaşadığı dönemin özellikleri ve onun ilmi kişiliği üzerinde etkili olmuştur. Gazzâli, kalb, akıl, ruh, nefs kavramlarını birbirine yakın anlamlarda kullanmıştır. Kalb-akıl ilişkisi Gazzâli'nin hayatında önemli değişiklikler meydana getirmiştir. Ona göre akıl, eşyanın hakikatini belli bir sınıra kadar anlar. Aklın anlamadığı metâfizik gerçeklikler kalb gözü denen bir algılamayla gerçekleşir. Kalbin nefsanî arzu ve isteklerden uzaklaştığı müddetçe melekût âlemine doğru bir yönü olacaktır. Bu noktada insanın kalbi önem arzetmektedir.Anahtar Kelimeler: Gazzâli, Kalb, Akıl, Ruh, Nefs.

Ghazzali who lived between XI and XII centuries is an Islamic thinker. Ghazzali is a scholar interpreting the era, in which he lived, with the idea of Ahl al-Sunnah. This scholar sheds light not only on his own time but also on today?s muslims. Ghazzali searched for the acceptable branches of the science of his time and specialized in the fields of those sciences. Ghazzali?s life was effective on the characteristics of time in which he lived and on his scholarly personality. Ghazzali used the meanings of heart, mind, spirit and soul concepts close to each other. Heart ?mind relationship gave rise to significant changes in Ghazzali?s life. In his mind, Intelligence can understand the truth of the goods up to a limited of certain moments. The metaphysical truths that cannot be understood by the mind of a humman being probably emerge from a perception of a heart-eye. As the heart of a human being diverges from humanly request and desire, it will have a way to heavenly realm. The heart of a human being is very important in this point of view.Key Words: Ghazzali, Heart, Mind, Spirit, Humanly Desire.
Heart-mind relationship of Ghazzali
Keywords: Din